COMPARATIVE STUDY OF THE IMAGE OF THE LOVER: BASED ON THE WORKS OF ABDURAHMAN JAMI "YUSUF AND ZULAYKHA" AND LORD BYRON "THE GIAOUR" - Fariza Tokhirova; Sabirjan Tokhirov (The Bioscan, 2025)
This article analyzes the epic "Yusuf and Zulaykha" by Abdurahman Jami, a representative of classical Eastern literature, and the image of the lover in the work "The Giaour" by Lord Byron, a representative of the West, based on a comparative approach. It embodies the features of the love motif, which are similar in form and different in content in Eastern and Western literature. In both works, the concepts of love, romance, anguish, spiritual search, and self-awareness occupy a central place. However, it is important that they differ in the specific features and expression of the love motif, and that this situation is manifested in the image of the lover. In the course of the research, it is analyzed how the concept of divine love, characteristic of classical Eastern art, is expressed in Jami's poem, and how the inner sufferings of the individual, characteristic of Western romanticism, are illuminated in Byron's work. Love has its own spiritual load in both works: one is a path of mystical purification and spiritual elevation, and the other is an inner struggle directed at human conscience and punishment, as well as a storm of complex emotional turmoil. On this basis, during the research, their character traits and qualities are compared. Through this comparative analysis, it is revealed how the image of the lover, expressed in these dastans, is formed differently in cultural and philosophical contexts. At the same time, the article draws conclusions about the commonalities and differences of the concept of love in Eastern and Western literature. KEYWORDS: Yusuf and Zulaykha, The Giaour, the image of a lover, comparative analysis, Eastern literature, Western literature, philosophy of love.